An Ultrathin Ferroelectric Perovskite Oxide Layer for High‐Performance Hole Transport Material Free Carbon Based Halide Perovskite Solar Cells. (14th November 2018) - Yang, Yinglong; Liu, Zhenghao; Ng, Wai Kit; Zhang, Lihua; Zhang, Hua; Meng, Xiangyue; Bai, Yang; Xiao, Shuang; Zhang, Teng; Hu, Chen; Wong, Kam Sing; Yang, Shihe
Abstract: The hole transport material (HTM) free carbon based perovskite solar cells (C‐PSCs) are promising for its manufactural simplicity, but they currently suffer from low power conversion efficiencies (PCE) largely because of the voltage loss. Here, a new strategy to increase the PCE by incorporating an ultrathin ferroelectric oxide PbTiO3 layer between the electron transport material and the halide perovskite is reported. The resulting C‐PSCs have achieved PCEs up to 16.37%, which is the highest record for HTM‐free C‐PSCs to date, mainly ascribable to the ferroelectric layer enhanced open circuit voltage. Detail measurements and analysis show an enhanced built‐in potential in the C‐PSCs as well as suppression of the non‐radiative recombination due to the ferroelectric PbTiO3 layer incorporation, accounting for the boosted V OC and photovoltaic performance. Abstract : An ultrathin ferroelectric oxide PbTiO3 layer is incorporated between the electron transport material and the halide perovskite in the hole transport material (HTM) free carbon‐based perovskite solar cell (C‐PSCs) . The achieved power conversion efficiency is as high as 16.37%, which is the highest record for HTM‐free C‐PSCs to date, mainly ascribable to the ferroelectric layer enhanced open circuit voltage.